Bank design: collection of student artworks - Ahmad, Nani Hartina; Roslan, Nur Fatiyah; Makrai, Nurin Elani; A Aziz, Azhar; Anuar, Zainab (Universiti Teknologi MARA, Kedah, 2023)
In making creative works, students need to have artistic thinking in producing their artwork. Therefore, the purpose of this study is to assist students in developing their ideas in order to create a great work of art with high aesthetic value. Since most students lack the initiative to think creatively while creating their works of art, they are hardly creative in producing good work. This research relates to ideation of bank design to compile the previous student projects to serve as a guide for inspiring students to create new designs. The purpose of this study was to determine the issues and skills that students faced when coming up with ideas for a piece of work. This study was conducted using qualitative methods to identify the challenges and competencies of students in developing ideas for a work. A conceptual framework was developed at the conclusion of this study to support students come out with new ideas.